STUDI EFEKTIVITAS PENGGUNAAN JEMBATAN PENYEBERANGAN ORANG (JPO) DI KAWASAN LAPANGAN MERDEKA MEDAN (STUDI KASUS : JL. PUTRI HIJAU DAN JL. GURU PATIMPUS) - Simanjuntak, Marganda Buala; -, Yulianto; Rajagukguk, Williater (ALUR :Jurnal Arsitektur, 2018)
Pedestrian Over Pass is one part of the pedestrian path that functions as a pedestrian crossing facility. Pedestrian Over Pass are located on highways with high vehicle intensity and railway lines. As a facility designated for pedestrians, the Pedestrian Over Pass should be effectively used. However, the phenomenon that occurs at this time is that there are many Pedestrian Over Pass that are not used by pedestrians, and they prefer to cross directly. Aside from not being used, many Pedestrian Over Pass are damaged and do not meet the standards of provision. Likewise, what happened in the Merdeka Field area in Medan, there are several Pedestrian Over Pass that are not used and have been damaged and cannot even be accessed. Therefore, researchers are interested in conducting research related to the effectiveness of using the Pedestrian Over Pass in the Merdeka Field area of Medan (Case study: Jalan Putri Hijau and Jalan Guru Patimpus). This study found that the effectiveness of using the Pedestrian Over Pass in research are are Low.